The development of federal crime prevention policy initiatives in Canada, 1992-1993. - Gervais, Christine L. M. (University of Ottawa (Canada), 1994)
Crime prevention has recently become a significant part of the rhetoric in the apparent transformation of criminal justice policy and practice. This thesis explores the implications of the Canadian federal crime prevention policy initiatives developed between 1992 and 1993. As a descriptive analysis, this thesis identifies the nature, the direction and the practical implications of the pending prevention policy initiatives aimed at reducing crime and victimization, and achieving community safety in Canada. A particular emphasis is placed on whether or not the proposed policy initiatives constitute a shift away from traditional reactive criminal justice responses, and towards a focus on proactive approaches. The analytical framework used derives from Stanley Cohen's (1985) views of social control and Ross Hastings' (1993a) Crime Prevention Typology. The author argues that the proposed "comprehensive" crime prevention strategy is limited in its capacity to significantly reduce crime and victimization because it emphasizes both inclusionary and exclusionary, as well as, both proactive and reactive measures of deviancy control. The author concludes that the federal crime prevention initiatives developed between 1992 and 1993 are not likely to result in significant changes in the delivery of social control. They may be considered, at best, a mere extension of the historical patterns of uneven progress in transformations of social control.
Keywords: Political Science, Public Administration.